The employment relationship in the UK public sector: A psychological contract perspective - Kessler, I; Coyle-Shapiro, J (2003)
The management of public servants has assumed increasing importance as public-service organizations are confronted with a rise in the demand for high-quality services in the context of limited resources. Much of the research on the treatment of public servants has focused on the notion of public-service motivation and whether the motives of public servants differ from those of private-sector employees. However, an organization's need to harness positive employee attitudes and behaviors as a means of coping with the pressures on public-service delivery encourages a focus on the factors influencing these attitudes and behaviors within the sector. We address this issue by drawing upon a psychological contract framework, which captures employee perceptions of the reciprocal exchange between employer and employee. This study investigates the relationship between the psychological contract and two outcomes: organizational commitment and organizational citizenship behavior using survey responses from 5,709 employees. The results support the underlying proposition that public-sector employees reciprocate the treatment they receive from their employers. Consequently, we argue that the psychological contract framework has some value in enhancing our understanding of public servants' attitudes and behaviors. We discuss the implications of our findings for the management of public servants, and we suggest that future research integrate individual predispositions and situational factors to provide a more comprehensive understanding of public servants' attitudes and behaviors.